TANTANGAN PEMANFAATAN ARTIFICIAL INTELLIGENCE TERHADAP KETAHANAN PRIBADI GENERASI Z - Mardiyah, Shoim; Sahadewa, Ngurah (JURNAL ELEKTROSISTA, 2023)
Generation Z, consisting of individuals born between 1997 and 2012, faces new challenges in harnessing technological advancements, particularly in the field of artificial intelligence (AI). Despite AI offering various benefits and significant potential, there are several challenges that need to be addressed to ensure the personal resilience of Generation Z in utilizing it. This research aims to analyze the challenges faced by Generation Z in leveraging AI and its impact on their personal resilience. Through qualitative data collection, the researchers analyze factors influencing the utilization of AI by Generation Z and its effects on aspects of mental well-being, privacy, and social intelligence, particularly in relation to the responsibility and ethics of AI utilization. The findings of this study identify several challenges encountered by Generation Z in the utilization of AI. Firstly, the uncertainty and rapid changes in AI technology can lead to anxiety and the inability to keep up with the latest developments. Secondly, the irresponsible use of AI can have negative effects on the mental well-being of Generation Z, such as excessive dependency or information manipulation. Thirdly, privacy and security concerns can pose serious threats when Generation Z uses AI applications that require access to their personal data. Lastly, the possibility of job displacement by AI can impact the career sustainability of Generation Z.